Intracavernous Stem Cell Injection for Erectile Dysfunction: Safety and Efficacy Review - Lubis, Ahmad Sulaiman; Makarim, Fadhli Rizal; Aldiosta, Pradipta Hadyan (International Journal of Cell and Biomedical Science, 2023)
Background: Erectile dysfunction is a common condition in men characterized by the inability to maintain an erectile state. Current treatment using phosphodiesterase-5 inhibitors treatment may leave significant side effects and effectivity problems in some patients. The use of stem cell transplantation in erectile dysfunction has been emerging as a replacement therapy for erectile dysfunction. The effectiveness of stem cell therapy for the treatment of erectile dysfunction has been investigated in several animal studies and one clinical trial in humans. The intracavernous injection is one of the methods to deliver stem cell treatment for erectile dysfunction besides intravenous and intraperitoneal. It was believed to improve erectile function by promoting cavernosal tissue regeneration, vascularization, and smooth muscle relaxation. However, the intracavernous injection of stem cells for erectile dysfunction treatment in clinical settings requires further investigation since its long-term efficacy and safety concerns regarding swelling, priapism, and fibrous plaque. Objective: This review aims to summarize the available evidence on the safety and efficacy of intracavernous stem cell injection for erectile dysfunction treatment in clinical studies only from PubMed. Conclusion: In conclusion, while the available evidence suggests that intracavernous stem cell injection is considered safe and effective for the treatment of erectile dysfunction, further large-scale clinical studies are needed to determine its long-term safety, efficacy, and optimal dosing regimens.